P105 Can patients enter the 'Standard Set' ICHOM parameters by completing electronic questionnaires?. (25th January 2019) - Walsh, A; Kantchuster, R; Matini, L; Wilson, J; Lepetyukh, M; Palmer, R; Brain, O; Keshav, S; Travis, S
Abstract: Background: The International Consortium for Health Outcomes Measurement (ICHOM) has created a 'Standard Set' for Inflammatory Bowel disease outcomes, but there is currently no system in place to collect these data. The ICHOM Standard Set for IBD is one of 26 ICHOM Standards in different disease areas established through a common methodology. 1 Methods: TrueColours ulcerative colitis (TCUC) is a comprehensive real-time web-based programme that, among other things, collects ICHOM parameters. 342 patients registered with TCUC were prompted (through email) to complete the ICHOM questionnaire. Results: 287/342 (84%) adherence rates to the ICHOM questionnaire: male 41%, distribution disease (proctitis 19%, left-sided colitis 21% and extensive colitis 30%, unsure 30%), level of education (none 5%, primary 2%, secondary 33% and tertiary 60%), smoking status (never 60%, ex-smoker 35% and current 5%). Extraintestinal manifestations included arthritis 15%, eye disease 2.4%, skin disease 1.4%, liver disease 1.4%. Hepatitis B was reported in 0.3%, previous tuberculosis in 1.4% and HIV in 0%. Over the previous 12 months, prednisolone use was reported in 22% for < 3 months and 15% for >3 months. Complications due to IBD interventions were reported in 10% (adverse reactions n = 21 (including 6 with pancreatitis), surgical complications n = 4, infection n = 4, malignancy n = 1, thrombosis n = 1, dermatological n = 2, diabetes n = 1). Complications resulting in hospitalisation occurred in n = 8 and prolonged hospitalisation (>10 days) in n = 4. Hospital admissions in the past 12 months: nil in 80%, 1 in 16%, 2 in 3%, ≥3 in 1%. The median estimated total length of stay was 5 days (IQR 6.0). Emergency Department visits in the past 12 months: nil in 78%, 1 in 13%, 2 in 7%, ≥ 3 in 2%. Colorectal cancer was reported by 2 (0.7%): neither patient was on a colorectal cancer surveillance scheme prior to this diagnosis. Conclusions: Collecting ICHOM parameters through patient-reported electronic questionnaires is possible. Adherence rates were good at 84%. Outcomes (eg, steroid use) are revealing. Used on a larger scale, this method would allow collection of ICHOM data and audit of quality improvement at an individual centre as well as comparison between centres. Reference 1. Kim A, Roberts C, Feagan BG, et al. Defining a standard set of patient-centred outcomes for inflammatory bowel disease—an international, cross-disciplinary consensus. J Crohns Colitis 2018;12:408–18.